A Young Male with Female Reproductive System - Amin, Md Robed; Das, Amit; Hossain, Md Murad; Zaman, Md Ferdous; Kabir, Ahmedul; Islam, Hafizul; Khondokar, MA Kashem (Journal of Medicine, 2010)
Patients with disorders of sexual differentiation possess discordance among sex chromosomes, gonads, sex hormones, and phenotypic sex. The most common of the phenotypic sex disorder is due to defect in enzyme for synthesis of steroids in adrenal cortex. A spectrum of phenotypes is observed in these cases. Here we present a case with features of female reproductive system in his body with male phenotype. As there was no trace of male sexual organs in all investigations but physical habitus was exclusively male with abundance of hair distribution the case was diagnosed as disorder of sex development (DSD) - female pseodoharmaphroditism. Keywords: Sex Differentiation Disorder, Disorders of Sexual Development, Pseudohermaphroditism DOI:10.3329/jom.v11i1.4276 J Medicine 2010: 11: 63-66